Non-animal-based options for animal-based foods- towards a systematic terminology - Abbaspour, Nazanin; Sanchez-Sabate, Ruben; Sabaté, Joan (Frontiers in Nutrition, 2023)
The market has seen a rapid increase in animal-free products intended to replace animal-based foods due to concerns for human health and environmental sustainability. However, there is a lack of consistent terminology for these products, with various terms being used interchangeably, creating ambiguity. To address this issue, we propose a systematic nomenclature that defines the most commonly used terms, namely alternative, substitute, replacement, and analog, along with examples of each. In this nomenclature, a substitute primarily serves a culinary purpose, while a replacement is concerned with nutritional properties. An analog strives to satisfy both culinary and nutritional attributes to closely mimic animal-based foods in terms of sensory, nutritional, and functional characteristics. The term "alternative" serves as an umbrella term encompassing all possibilities. This work aims to promote a clearer understanding of such products and their intended use and facilitate a unified use of terminology across disciplines. This will also enable informed decision-making for consumers and greater transparency in the food industry. The health and environmental implications of these products are not discussed in this perspective.